Induksi Pematangan Gonad dengan Ovaprim-C: untuk Penyediaan Benih Belut Sawah (Monopterus albus) Berkelanjutan - Priyo Susatyo; Sugiharto Sugiharto; Elly Tuti Winarni (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
Rice eel (Monopterus albus Zuiew), have economical value is high in Banyumas, national to international markets, but rarely is grown intensively, the seed is still dependent on the catch. Reproduction of swamp eel unlike other fish species in the presence of phase teleostei intersex / hermafroditus and in nature only spawn once a year. This study will seek to accelerate the scale seed production with natural canvas with several techniques triggers lust and sex organ maturation eels based preparedness aspects of reproductive anatomy, hormones estradiol and testosterone profiles and the intrinsic need for hormonal regulation and the mechanism for the reproductive cycle of the eel rice. In the first year aims to determine (1) the profile of estradiol and testosterone hormonal parent during the natural reproductive cycle, (2) histologic gonadogenesis (development of the testes and ovaries) eel rice during the natural reproductive cycle was evaluated by measuring fecundity. Results: In the control group, body weight gradually decreased during the study. Unlike the control group, the treatment groups were observed every two weeks showed an increase in body weight; Results of the study, in the control group (A0), the value of female eels GSI average of the first two weeks until the fourth two weeks is 0.67 % and 1.78%. While the treatment group A1 was 1.42% - 4.28% (DM-1 s / d DM-4), for the treatment A2 GSI average value is 2.52% - 7.05%; fecundity eggs increased during induction period; calibration titer two types of hormones in the first two weeks to the fourth two weeks showed improvement when compared with the control group; histological profile of rice eel gonad after induction of ovaprim-C show that up to the fourth two weeks, gonad has reached late-stage yolk globule (advanced primary oocyte), even the most mature oocyte has reached the stage: in male eels up to the fourth two weeks has reached the stage of spermatozoa